Pengembangan Perangkat Pembelajaran Kimia SMA dalam Model Discovery Learning untuk Meningkatkan Sikap Ilmiah dan Hasil Belajar Peserta Didik - Rosnawati, Rosnawati; Sugiarti, Sugiarti; Sulastry, Taty (Chemistry Education Review (CER), 2023)
This study is a development research that aims to develop and produce high school chemistry learning tools in discovery learning model on acids and bases materials. The development model employed a 4-D model from Thiagarajan. The limited trial of learning tools in the discovery learning model was conducted at SMAN 6 Makassar with the research subject of grade XI MIPA 3 with 25 students. Data collection techniques were non-test and test techniques. The results of the study indicate that: (1) the process of developing learning tools employed a 4-D model which included 4 stages, namely: (a) the definitng stage (define), (b) the design stage, (c) the development stage (develop), and (d) the dissemination stage (disseminate); (2) the learning tools are valid, practical and effective. The learning tools have met the validity criteria including the RPP, LKPD, and THB, each of which is in valid category. The learning tools are stated as practical because the implementation of learning tools is in fully implemented category and the teacher and students’ responses to learning tools are in very practical category. The learning tools are stated as effective because they meet the effectiveness criteria. The results of the analysis of students' scientific attitudes are in very good category with 83.12% per meeting and increase to 83.47% at the end of the meeting, while the learning outcomes has classical completeness by 84%.